Leaving the Parental Home in Russia: Intergenerational Aspects - Dolgova, Alina; Mitrofanova, Ekaterina (Journal of Economic Sociology, 2015)
Leaving home is a key life event in the transition to adulthood, but it has been relatively less explored in demographic and sociological studies of Russia. The modernization of socio-demographic behavior which started in the 1960s in Europe is described as the Second Demographic Transition. This began in Russia only in the 1990s. One characteristic of the Second Demographic Transition is that young people spend more time on education, career building, and self-realization: they use a wide range of opportunities of today’s world. Current young adults prefer non-marital unions, which postpones starting a family. As a result Russian young adults (born in 1975–1986) tend to leave their parents’ home at later ages than their predecessors (born in 1930–1974). The aim of this research is to examine the changes in the timing of leaving home in the perspective of four Russian generations, and set up a new model for understanding leaving home in Russia. At what age do today’s young people leave the parental home, compared with previous generations? What factors influence the age at which children leave their parents’ home? To answer these questions, we used the panel data of the Russian part of Generations and Gender Survey (GGS-panel: 2004, 2007, and 2011). We analyze the leaving home experience of men and women aged 15–35 years, who were born in 1930–1986. The sample size is in total 5451 respondents. Our main method of analysis is event history analysis (Cox regressions, life tables). The data illustrate that generation cohort and social variables influence the strategies of leaving home. The main finding of our research is that leaving the parental home depends on generation, and the changes of the model of leaving home are similar to European countries which experienced the Second Demographic Transition.